Integration of financial supervision - Helena Holopainen (Bank of Finland, 2007)
The emergence of financial conglomerates and multinational financial institutions as well as the development of new financial products have raised concerns as to the ability of separate sectoral supervisors and different national authorities to effectively oversee financial markets. Concentrating on the European situation, this paper addresses these concerns by putting special emphasis on the role of organizational form in the supervisory process of financial institutions. I will first outline the developments that have led to increasing pressures to reform the current supervisory systems in Europe, proceed to discuss both some common and specific aspects of supervision of financial conglomerates and multinationals, and, finally, examine the challenges related to the integration of supervision. Using theoretical framework derived from economic theory, this paper points that multitude of factors (eg, several multitasking-related concerns) are likely to affect the effectiveness of integrated supervision.
URN:NBN:fi:bof-20140807389
Keywords: G21; G22; G28; 330; financial supervision; financial conglomerates; multinationals; integration of supervision